Polymorphism Rs2421943 of the Insulin-Degrading Enzyme Gene and the Risk of Late-Onset Alzheimer's Disease - Šerý, Omar; Zeman, Tomáš; Hálová, Alice; Janout, Vladimír; Janoutová, Jana; Lochman, Jan; Balcar, Vladimir J (Current Alzheimer research, 2022)
BACKGROUND: Insulin-degrading enzyme (IDE) is a widely distributed Zn2+-binding metalloprotease that cleaves multiple short and medium-sized peptides prone to form β-structures. These include insulin and amyloid-β peptides. Accumulation and fibrillation of amyloid-β peptides leading to the formation of amyloid plaques is a characteristic sign of Alzheimer's disease (AD) pathology. OBJECTIVE: The study investigated the rs2421943 single nucleotide polymorphism (SNP) of the IDE gene as a risk factor for MCI (mild cognitive impairment) and AD. METHODS: Two independent groups of 1670 patients and controls were included. The AD group consisted of 595 patients and 400 controls; the MCI group involved 135 patients and 540 matched controls. PCR and restriction fragment length analysis were used to analyze the rs2421943 polymorphism. Using the miRBase and RNA22 prediction tools in silico indicated that the rs2421943 polymorphism is a potential target for a specific miRNA (hsa-miR-7110-5p). RESULTS: AG and GG genotypes of rs2421943 significantly increased the risk of AD, and the AG genotype increased the risk of MCI. It seems the G allele both increases the risk of AD and accelerates the transition through the MCI phase. In silico study revealed that rs2421943 is inside the sequence binding miRNA hsa-miR-7110-5p. The polymorphism could affect the rate of IDE pre-RNA (heterogeneous nuclear RNA, hnRNA) processing, resulting in slower translation, lower levels of IDE, deficient removal of amyloid-β fragments, and greater risk of and/or accelerated progression of AD. CONCLUSION: GG and AG genotypes of the single nucleotide polymorphism rs2421943 of insulindegrading enzyme gene increase the risk of AD and MCI.
Keywords: amyloidní beta-protein; Insulysin; jednonukleotidový polymorfismus; Amyloid beta-Peptides; MicroRNAs; lidé; Polymorphism, Single Nucleotide; single nucleotide polymorphisms; mikro RNA; amyloid-β peptide; mild cognitive impairment; Alzheimerova nemoc; Humans; insulinasa; type-2 diabetes mellitus; insulin-degrading enzyme; Alzheimer’s disease; Alzheimer Disease